Pertanggungjawaban Perseroan Terbatas Terhadap Kepailitan dalam Perjanjian Pinjaman (Putusan Nomor 34/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst dan Putusan Nomor 38/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst) - Nanik Indah Setyani; Anwar Budiman; Saefullah Saefullah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the legal liability of a Limited Liability Company (LLC) before and after bankruptcy, with a focus on the roles of the board of directors, board of commissioners, and the curator appointed by the Commercial Court. Prior to bankruptcy, the liability for the company's obligations rests primarily with the board of directors and the board of commissioners, especially when debts arising from binding agreements remain unpaid. In situations where the company is unable to fulfill its payment obligations, and such inability is confirmed by a final court ruling, responsibility for managing and settling the company’s debts and assets is transferred to a court-appointed curator. The research analyzes the legal framework governing the curator’s authority, which operates under the supervision of a supervisory judge from the Commercial Court. The curator acts as the sole party responsible for handling the bankrupt entity’s obligations to creditors, ensuring compliance with applicable bankruptcy laws. This study uses a normative juridical approach, relying on legislation, case law, and legal doctrine to examine the extent of responsibility at each stage of the bankruptcy process. Special attention is given to the legal considerations of the Central Jakarta Commercial Court in Decisions Number 34/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst and Number 38/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst. Both rulings are found to be appropriate, as they meet the legal requirements for declaring an LLC bankrupt based on verified facts and circumstances. The findings underscore the importance of distinguishing between pre-bankruptcy liabilities—borne by company management—and post-bankruptcy responsibilities, which are entirely managed by the appointed curator. This clear allocation of responsibility ensures creditor protection, maintains judicial oversight, and upholds the principles of fairness and legal certainty in bankruptcy proceedings